Convergences among Image, Technology, and Design at PPGD/EBA/UFRJ - Silva, Jofre; Esperança, Claudio; Pereira, Clorisval; Kosminsky, Doris; Heinrich, Fabiana Oliveira; Grimaldi, Madalena Ribeiro; Ribeiro, Marcelo; Soares, Lilian; Sánchez, Pedro (DAT Journal, 2026)
This article presents the Research Line Image, Technology, and Project of the PPGD/EBA/UFRJ, highlighting its contribution to design research by recognizing project practice as knowledge production and the image as a critical field of inquiry. Grounded in the inseparability of theory and practice, the Research Line articulates design, art, technology, and critique within an approach that examines visual objects and technologies beyond their instrumental uses. The text outlines the theoretical and methodological guidelines of the Research Line through the groups and laboratories led by its faculty members – LabVis, LabCrit, PHADEC, CRIAR, Imagem(i)matéria, Táticas Visuais, Palomar, and LabImpacto – which investigate data visualization, digital culture, photography, perception, drawing, image circulation, memory, and social innovation, always considering the ethical, political, and cultural dimensions of contemporary technologies. These investigative approaches conceive design as a historically situated cultural practice, moving away from strictly technological or market-driven perspectives and expanding design thinking beyond traditional problem-solving models, valuing experimentation, reflective practices, and meaning-making in order to educate researchers capable of problematizing methods, challenging normative models, and producing situated knowledge within the Brazilian context.